Patient and General Practitioner characteristics influencing the management of non-insulin-treated diabetes mellitus: A cross-sectional study in Italy. (June 2016) - Ferroni, Eliana; Casotto, Veronica; Pigato, Mara; Scroccaro, Giovanna; Corti, Maria Chiara; Fedeli, Ugo; Saugo, Mario
Highlights: 40% of non-insulin treated patients with diabetes attended Diabetes Clinics. More than 70% had at least 1 HbA1c test and about 40% 2 tests yearly. 67% had a lipid profile assessment, less than a half underwent microalbumin test. Younger patients, immigrants and patients not attending Diabetes Clinics were less monitored. Female, younger and proactive GPs showed a better diabetes management. Abstract: Aims: We assessed the influence of patient and General Practitioner (GP) characteristics on the adherence to process of care indicators for non-insulin-treated type 2 diabetes management in the Veneto Region (northeastern Italy). Methods: Among non-insulin-treated diabetic patients aged 18–84 years identified by multiple information sources, we assessed the measurement of glycated hemoglobin, microalbumin, and lipids through the year 2013. Patients' variables included gender, age, citizenship, and the attendance to Diabetes Clinics, while GP characteristics were gender, age and an attitude score derived from a questionnaire. The influence of patient and GP variables were investigated through multilevel regression with the execution of two HbA1c tests in 2013 as the outcome. Results: Out of 139, 935 study subjects, more than 70% had at least one HbA1c test in 2013; this percentage decreased to about 40% for two HbA1c examinations. 67% of patients had an assessment of lipid profile, while 45% underwent a microalbumin test. These percentages were lower for immigrant patients and increased with age until the 65–74 years age class. Patients attending Diabetes Clinics were usually better monitored than those who did not. In this latter group, female gender (risk ratio 1.08, 1.02–1.14), younger age (risk ratio 1.15, 1.06–1.25) and high attitude score of GPs (risk ratio 1.20, 1.13–1.27) were associated with a better management. Conclusions: Both patient and GP variables influence the adherence to process of care indicators. The implementation of effective strategies of disease management at the primary care level may improve the control of glycemic and cardiovascular risk factors.